DEVELOPMENT OF LEARNER WORKSHEET (LKPD) USING RME APPROACH BASED ON MANDAILING CULTURE TO IMPROVE STUDENT LITERACY - Nurdalilah Nurdalilah; Adek Nilasari Harahap (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The purpose of this research is to develop a valid, practical, and effective Learner Worksheet (LKPD) in improving students' literacy skills. This study used the research and development method with the ADDIE (Analysis, Design, Development, Implementation) development model. Data collection instruments included validation sheets, learner and teacher response questionnaires, activity observation sheets, motivation questionnaires, and literacy tests. This study involved Grade VII students and mathematics teachers in a private junior high school in Padangsimpuan.Based on the Realistic Mathematics Education (RME) approach and local culture, LKPDs were developed that showed a high level of validity in terms of media, materials, and language. Positive responses from students and teachers indicate the practicality of the LKPD. The effectiveness of the LKPD can be seen in the improvement of students' literacy skills as evidenced by observations, motivation questionnaires, and literacy tests.Tujuan penelitian ini adalah untuk mengembangkan Lembar Kerja Peserta Didik (LKPD) yang valid, praktis, dan efektif dalam meningkatkan kemampuan literasi siswa. Penelitian ini menggunakan metode Research and Development dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation). Instrumen pengumpulan data meliputi lembar validasi, angket respon peserta didik dan guru, lembar observasi aktivitas, angket motivasi, serta tes kemampuan literasi. Penelitian ini melibatkan siswa kelas VII dan guru matematika di sebuah SMP Swasta di Padangsimpuan, menghasilkan LKPD berbasis pendekatan Realistic Mathematics Education (RME) dan budaya lokal yang menunjukkan tingkat kevalidan tinggi dalam aspek media, materi, dan bahasa. Respon positif dari peserta didik dan guru menunjukkan praktikalitas LKPD. Efektivitas LKPD terlihat dari peningkatan kemampuan literasi siswa, sebagaimana dibuktikan melalui observasi, angket motivasi, dan tes literasi.